2020
DOI: 10.1001/jamanetworkopen.2019.20833
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Activity of PD-1 Checkpoint Inhibitor Combination Therapies Reported in Clinical Trials

Abstract: IMPORTANCE Because cancer drugs given in combination have the potential for increased tumorcell killing, finding the best combination partners for programmed cell death 1 (PD-1) checkpoint inhibitors could improve clinical outcomes for patients with cancer.OBJECTIVE To identify optimal strategies for combining PD-1 immune checkpoint inhibitors with other cancer therapies. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study compiled 319 results from 98 clinical trials testing PD-1 pathway inhibitors alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…We found that the duration of response (as measured by PFS) as well as changes in tumor volume were precisely consistent with independent action. Additional evidence for independent action in PD-1 inhibitor combinations was recently reported by Schmidt et al 11 based on analysis of objective response rates. In this paper we analyze PFS data from all clinical trials of ICI combination therapies as of April 2020 for which data on single agent and combination arms are available and look for evidence of additive or synergistic drug interaction.…”
Section: Introductionmentioning
confidence: 55%
“…We found that the duration of response (as measured by PFS) as well as changes in tumor volume were precisely consistent with independent action. Additional evidence for independent action in PD-1 inhibitor combinations was recently reported by Schmidt et al 11 based on analysis of objective response rates. In this paper we analyze PFS data from all clinical trials of ICI combination therapies as of April 2020 for which data on single agent and combination arms are available and look for evidence of additive or synergistic drug interaction.…”
Section: Introductionmentioning
confidence: 55%
“…We found that the duration of response (as measured by PFS) as well as changes in tumor volume were precisely consistent with independent action. Additional evidence for independent action in PD-1 inhibitor combinations was recently reported by Schmidt et al 11 based on analysis of objective response rates. In this paper we analyze PFS data from all recent clinical trials of ICI combination therapies for which data on single agent and combination arms are available and look for evidence of additive or synergistic drug interaction.…”
Section: Introductionmentioning
confidence: 55%
“…The intermediate analysis showed that this regimen has great treatment potential, with an ORR of 63%, CR of 31%, and a DCR of 63% [46]. In a cross-sectional study of 98 clinical trials testing ICIs alone or in combination with other agents, the most compatible partner of ICIs would be the platinum chemotherapy or an anti-angiogenetic inhibitor, supporting combination treatment utilizing an angiogenetic inhibitor and platinum chemotherapy with ICIs [47]. Currently, as described in the previous section regarding anti-angiogenetic inhibitors, several trials using such treatment strategy are ongoing: the phase III COMMIT trial [37] and the phase II AtezoTRIBE trial [38].…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 99%